PENERAPAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENUMBUHKAN AKTIVITAS KOLABORATIF PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR - Novita Fitriyani; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The study aims to describe the application of Cullturally Responsive Teaching (CRT) to foster collaborative activities in Pancasila Education learning for elementary school student. This research uses a qualitative descriptive aaproach. The research was conducted at SD Negeri 02 Ngepungsari, Karanganyar Regency. Data collection techniques used were observation, interviews, and documentation. Data validity was ensured trough source triangulation, technique triangulation, and time triangulation. Data Analysis used the interactive model of Miles And Huberman, which includes data reduction, data presentation, and conclusion drawing. The result show that: (1) The application of CRT in Pancasila Education was carried out through three stages: planning, implementation, and closing. In the planning stage, the teacher prepared teaching modules and learning media in the form of videos and three dimensional dioramas decipting the diversity of Indonesian culture. In the implementation stage, the teacher connected the learning material with students’s daily lives and local cultural backgrounds. In the closing stage, the teacher led students in summarizing the material together. (2) Students’s collaborative activities, where students actively exchanged opinions, cooperated in completing tasks, and showed attitudes og mutual respect. It is concluded that the application of CRT effectively fosters collaborative activities and strengthens the internalization of Pancasila values in elementary scholl students